Air Embolism During TEVAR: Liquid Perfluorocarbon Absorbs Carbon Dioxide in a Combined Flushing Technique and Decreases the Amount of Gas Released From Thoracic Stent-Grafts During Deployment in an Experimental Setting. (February 2019) - Rohlffs, Fiona; Trepte, Constantin; Ivancev, Krassi; Tsilimparis, Nikolaos; Makaloski, Vladimir; Debus, E. Sebastian; Kölbel, Tilo
Purpose: To investigate the influence of flushing thoracic stent-grafts with carbon dioxide and perfluorocarbon on the amount of gas released during stent-graft deployment in thoracic endovascular aortic repair (TEVAR).Materials and Methods: Ten TX2 ProForm thoracic stent-grafts were deployed into a water-filled container with a curved plastic pipe and flushed sequentially with carbon dioxide, 20 mL of liquid perfluorocarbon (PFC), and 60 mL of saline. Released gas was measured using a calibrated setup. The volume of released gas was compared with the results of an earlier published reference group, in which identical stent-grafts were flushed with 60 mL saline alone as recommended in the instructions for use.Results: The average amount of gas released in the test group was 0.076 mL, significantly lower (p<0.001) than the mean 0.79 mL of gas released in the reference group. Big bubbles appearing at the tip of the sheath when deployment was started were seen in all grafts of the reference group but in only 2 of the test group stent-grafts. Small bubbles were less frequent in the test group.Conclusion: The amount of gas released from thoracic stent-grafts during deployment can be influenced by different flushing techniques. The use of PFC in addition to the carbon dioxide flushing technique reduces the volume of gas released during deployment of tubular thoracic stent-grafts to a few microliters. This significant effect is presumably based on the high solubility of carbon dioxide in perfluorocarbon and could be a potential future approach to lower the risk of cerebral injury and stroke from air embolism during TEVAR.